2008
DOI: 10.2165/00128071-200809010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Skin Hydration Evaluation Sites and Correlations among Skin Hydration, Transepidermal Water Loss, SCORAD Index, Nottingham Eczema Severity Score, and Quality of Life in Patients with Atopic Dermatitis

Abstract: In AD research, three sites on the forearm appear to be convenient for determination of SH and TEWL. This is the first report to demonstrate that significant correlations are obtained among acute and chronic scores of AD disease severity, quality of life, and the bioengineering parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 23 publications
6
66
0
1
Order By: Relevance
“…In 2008, two groups of researchers, Hon et al 60 and Gupta et al, 61 showed a correlation between TEWL and SCORAD in children, proving that there is an association between injury to the skin barrier measured by TEWL and the clinical intensity of the disease.…”
Section: Authorsmentioning
confidence: 99%
“…In 2008, two groups of researchers, Hon et al 60 and Gupta et al, 61 showed a correlation between TEWL and SCORAD in children, proving that there is an association between injury to the skin barrier measured by TEWL and the clinical intensity of the disease.…”
Section: Authorsmentioning
confidence: 99%
“…A modified skin barrier with increased transepidermal water loss and reduced hydration of the skin is a characteristic feature of AD patients, whereupon the extent of barrier dysfunction correlates with AD severity [1] . The epidermis functions both as a physical barrier and as an active immunological organ.…”
mentioning
confidence: 99%
“…Environmental allergens' penetration through the skin is facilitated by the skin barrier impairment what causes xerosis and transepidermal water loss (TEWL) increase [2][3][4][5]. As AD is a chronic disease, there are many factors responsible for exacerbations during the course of the disease, including stress.…”
Section: Introductionmentioning
confidence: 99%
“…It can cause some psychological disturbances, such as stigmatization, discrimination and social isolation. Affected individuals have been reported to suffer from anxiety, emotional excitability and depression [4,[9][10][11][12]. Health-related quality of life (HRQoL) is correlated with the disease duration: the longer the disease duration, the lower HRQoL in allergo-dermatological patients is [13].…”
Section: Introductionmentioning
confidence: 99%